PENGARUH PENCAIRAN ATAS PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA JAKARTA KRAMAT JATI - Pujiwidodo, Dwiyatmoko (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
A source of revenue from the tax is the most potential to increase state revenue each year. To increase tax revenues is then held tax collection. But in doing this tax the government often find some obstacles. One of them is the tax arrears. To overcome these obstacles it is necessary to collection action. In this study the authors used quantitative analysis, determination, regression and hypothesis testing, which became independent variable in this study is liquefaction top billing with a letter of reprimand (X1), liquefaction top billing forced letter (X2), and the dependent variable is the tax revenue ( Y). This research was conducted in KPP Pratama Jakarta Kramat Jati. The purpose of this study was to determine the effect of liquefaction top billing with warning letters and letters to tax revenues forced the period January 2012 to December 2014. The results of this study is that the disbursement letter of reprimand and forced letter effect on tax revenue. It can be seen from the test results f simultaneously that show the results of 0.000 (<0.05), which showed no significant effect. The amount of R square of 0.426 which only shows that the melting of the top billing with a letter of reprimand and forced only effect of 0.426% of the tax revenue, while 99.574% influenced by other variables Keywords : Warning Letter, Letter Forced, Tax Revenue